2016
DOI: 10.1371/journal.pntd.0004417
|View full text |Cite
|
Sign up to set email alerts
|

Climate and the Timing of Imported Cases as Determinants of the Dengue Outbreak in Guangzhou, 2014: Evidence from a Mathematical Model

Abstract: As the world’s fastest spreading vector-borne disease, dengue was estimated to infect more than 390 million people in 2010, a 30-fold increase in the past half century. Although considered to be a non-endemic country, mainland China had 55,114 reported dengue cases from 2005 to 2014, of which 47,056 occurred in 2014. Furthermore, 94% of the indigenous cases in this time period were reported in Guangdong Province, 83% of which were in Guangzhou City. In order to determine the possible determinants of the unprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 48 publications
5
103
1
Order By: Relevance
“…We inferred that it was probably due to the climate that year, because climate significantly influences viruses, mosquitoes and hosts. A large number of studies on the effect of climate on dengue morbidity have been completed in China and abroad Cheng et al, 2016;Ebi and Nealon, 2016;Quam et al, 2016). These studies indicated a preferred temperature range for DENV reproduction from 18.0 to 33.2 °C.…”
Section: Discussionmentioning
confidence: 99%
“…We inferred that it was probably due to the climate that year, because climate significantly influences viruses, mosquitoes and hosts. A large number of studies on the effect of climate on dengue morbidity have been completed in China and abroad Cheng et al, 2016;Ebi and Nealon, 2016;Quam et al, 2016). These studies indicated a preferred temperature range for DENV reproduction from 18.0 to 33.2 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Fig 3 shows the weekly temperature and precipitation data for Guangzhou. We use climate data for Guangzhou, given the city’s predominant role in this outbreak with approximately 83% of the total cases [33]. …”
Section: Methodsmentioning
confidence: 99%
“…In Guangdong, on every Friday afternoon from September 24th to late November in 2014, insecticidal fogging and mosquito repellents were used to kill mature mosquitos with a fraction α m ; Water containers were also emptied to remove immature mosquitos and destroy their breeding sites with a fraction α A [33]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations